Recovery of human interferon alpha-2b from recombinant Escherichia coli using alcohol/salt-based aqueous two-phase systems - Lin, Yu Kiat; Ooi, Chien Wei; Tan, Joo Shun; Pau, Loke Show; Ariff, Arbakariya; Ling, Tau Chuan (Elsevier, 2013)
The purification of intracellular human recombinant interferon-alpha2b (IFN-α2b) from Escherichia coli (E. coli) was studied using alcohol/salt aqueous two-phase system (ATPS). The influences of nine biphasic systems comprising alcohol-based top phase (ethanol, 1-propanol and 2-propanol) and salt-based bottom phase (ammonium sulfate, di-potassium hydrogen phosphate and monosodium citrate) on IFN-α2b purification were studied. The results showed that the optimum condition for purification of IFN-α2b was achieved in ATPS composed of 18% (w/w) 2-propanol with 22% (w/w) ammonium sulfate in the presence of 1% (w/w) sodium chloride (NaCl). The purified IFN-α2b recorded a purification factor (PF) of 16.24 with the yield of 74.64%.